Optimization and In Vitro Evaluation of Alginate: Hydroxypropyl Methylcellulose Microspheres Loaded Tetanus Toxoid Vaccine - Saravana Kumar, A.; Renuka Devi, P.; Mani, K.R. (Asian Journal of Chemistry, 2011)
Tetanus toxoid loaded alginate microspheres has been developed and investigated for their feasibility in release by in vitro release. Tetanus toxoid was stabilized, encapsulated in microspheres prepared from alginate by using protein stabilizer (sucrose). Alginate microspheres were prepared by W/O/W double emulsion method. The developed materials were characterized for their size, surface morphology, protein loading efficiency, release of tetanus toxoid-loaded alginate microspheres (TTAL). The morphology of TTAL was smooth and spherical in shape with a diameter of around 10 μm. The TTAL were evaluated for vaccine entrapment and the in vitro release study was carried out by differing stabilizer sucrose concentration (5, 7, 10 and 12 % w/v) for the period of 70 days. Antigen release from microspheres was determined by ELISA. Based on these findings, 10 % w/v of sucrose shows good sustained antigen delivery with polymer degradation and the release of tetanus toxoid was increased. This approach should have potential application in the field of vaccine delivery.